Peran Ganda Perempuan dalam Dinamika Ekonomi dan Keluarga di Kota Bandung - Syasya Nur'aini Riswandy; Mirna Nur Alia Abdullah (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2024)
This research aims to look at the impact of women's dual role in economic and family dynamics and its impact on women's survival. Researchers used a literature study method which was strengthened using qualitative methods in the form of interviews. This literature study method is the collection of information from various journals, articles, and theses. Apart from that, qualitative methods in the form of interviews were used to strengthen the results of the literature study. Interviews were conducted online via chat with resource persons who work as school employees, nurses, and also teachers. Based on the results of interviews, it was found that the dual roles experienced by women did not burden the lives of housewives. Urgent economic needs force mothers to participate in providing household needs. Women also play an important role in improving family welfare. Therefore, researchers provide an overview of the effectiveness of dual roles in economic and family dynamics.